Benzo(a)pyrene and Gut Microbiome Crosstalk: Health Risk Implications - Intan Rizki Mauliasari; Hee Ju Lee; Song Yi Koo; Emmanuel Hitayezu; Anh Nguyen Thi Kieu; Sang-Min Lee; Kwang Hyun Cha (Toxics)
This review delves into the impact of benzo(a)pyrene (B(a)P), which is a toxic and pervasive polycyclic aromatic hydrocarbon (PAH) and known carcinogen, on the human health risk from a gut microbiome perspective. We retrieved the relevant articles on each PAH and summarized the reporting to date, with a particular focus on benzo(a)pyrene, which has been reported to have a high risk of gut microbiome-related harm. B(a)P exposure can compromise the homeostasis of the gut microbiota, leading to dysbiosis, a state of microbial imbalance. The consequences of B(a)P-induced gut dysbiosis can be far-reaching, potentially contributing to inflammation, metabolic disorders, and an increased risk of various diseases. Additionally, due to the strong coupling between B(a)P and microparticles, the toxicity of B(a)P may be further compounded by its reaction with strong gut disruptors such as micro-/nanoplastics, which have recently become a serious environmental concern. This review summarizes current research on the impact of B(a)P on the gut microbiome, highlighting the intricate relationship between environmental exposure, gut health, and human disease. Further research is necessary to elucidate the underlying mechanisms and develop effective strategies to mitigate the adverse health effects of B(a)P exposure.